The 45 and Up Study: reflecting on contributions to global evidence using case studies on cardiovascular disease and smoking - Ellie Paige; Jennifer Welsh; Grace Joshy; Marianne F Weber; Emily Banks (Sax Institute, 2022)
Background/objective: To describe the attributes that have underscored the success of the 45 and Up Study (the Study) and demonstrate its value by reflecting on two case studies: our research on socioeconomic inequalities in cardiovascular disease; and the harms of smoking. Type of program or service: The Study is the largest study of healthy ageing in Australia, and one of the biggest in the world; it recruited 267 357 participants aged 45 years and older from NSW, Australia from 2005 to 2009. For more than 15 years, it has provided high-quality evidence on a broad range of public health related issues. We reflect on its value using two research case studies. Results: Four key attributes have enabled the success of the Study: its establishment as a collaborative resource, including early and ongoing engagement with researchers and policy and practice partners; its large scale, which makes it ideally suited to quantify associations between risk factors and health outcomes, including for high priority populations; high quality self-reported survey data; and linkage to routinely collected administrative data, including specialised data. Novel Australian findings on cardiovascular disease (CVD) and smoking illustrate how the Study has contributed to national and international evidence, informing policy and practice. Results on CVD demonstrated individual-level education-related inequalities in CVD incidence and mortality, and greater use of pharmacotherapy for secondary prevention of CVD, in people with low versus high socioeconomic status. In terms of smoking, Study data showed that current smokers have around three times the mortality of never-smokers; that even "light" smoking of <14 cigarettes per day doubles mortality; that quitting is beneficial at any age; that smoking increases the risk of multiple cancer types; and that smoking causes half of deaths in Aboriginal and Torres Strait Islander adults aged 45 years and over and more than one-third of all deaths in the population. This evidence has been used by more than 50 government and non-government organisations, including contributing to legislation, policy and national and international monitoring and reporting. Lessons learnt: The Study has fulfilled a vital role in public health research and practice in Australia, providing locally relevant data to enable research on health issues of importance, including health inequity. Through ongoing partnerships, the Study's data has contributed to international scientific evidence and been used to inform public health policy and practice. It has also been used as a focus for collaboration and capacity building.